Traditional ecological knowledge and biodiversity conservation: the medicinal plants of the Dayak Krayan people in Kayan Mentarang National Park, Indonesia - Rina Susanti; Ervizal A.M. Zuhud (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Susanti R, Zuhud EAM. 2019. Traditional ecological knowledge and biodiversity conservation: the medicinal plants of the Dayak Krayan people in Kayan Mentarang National Park, Indonesia. Biodiversitas 20: 2764-2779. Traditional ecological knowledge and biodiversity conservation can support one another for management of national parks in Indonesia as some such areas established in customary areas. This quantitative ethnobotany study aims to find the correlation of traditional ecological knowledge of medicinal plants of the Dayak Krayan people to biodiversity conservation in Kayan Mentarang National Park (KMNP), North Kalimantan, Indonesia. The research method used key informant interviews, transect walks, and questionnaire interviews. There were about 51 and 42 medicinal plants in Wa’ Yagung and Pa’ Padi respectively, which most used in life form of herb and tree, and to treat digestive system and infestations. Moreover, the important species are trees Alstonia scholaris and Cinnamomum cuspidatum, and vine Aristolochia sp. which grow in primary forest, while shrub Melastoma malabathricum in young secondary forest. There were significant differences in knowledge and use regarding age and gender groups, which older groups tend to possess higher values. The linking concept is proposed by using a review of three stimuli NUR (Natural-Usefulness-Religious) pro-conservation tool of traditional ecological knowledge and biodiversity conservation. The authorities’ stakeholders in KMNP will have to emphasize the traditional ecological knowledge in short or long-term management plan to achieve the objective of collaborative management in this national park.